Development of norms of physical ability tests of students aged 13 -18 years - Lukas Maria Boleng; Michael Johannes Hadiwijaya Louk; Al Ihzan Tajuddin; Ronald Dwi Ardian Fufu; Veramytha Maria Martha Flora Babang; I Nyoman Wahyu Esa Wijaya; Salmon Runesi (Jurnal Cakrawala Pendidikan, 2023)
Evaluation of physical abilities in sports is one of the necessary components in determining achievement and improving sports achievement for all sports. Physical ability includes two components, namely the physical fitness component and the motor fitness component. Physical fitness consists of muscle strength (strength), flexibility (flexibility), muscle endurance (endurance), cardiovascular-respiratory endurance. The components of fitness include speed, coordination, agility, power strength and balance. The purpose of this research is to produce a norm test that fits the physical characteristics of students aged 13-18 year. The specific objective of this research is to obtain an effective physical ability test instrument that is suitable for the characteristics of the ages of 13-18 years and to produce students' physical ability test norms. The test development in this study was designed to have a fairly high level of accuracy, cheap, and easy to implement by anyone. Based on the results of the FGD (Focus Group Discussion), trainer opinions and expert recommendations, the researchers developed the existing test norms, that can predict the type of test that is appropriate for athletes aged 13-18. The physical test developed consists of 10 test item components, including Endurance, Strength, Agility, Speed, Flexibility, Coordination, Balance, Accuracy. accuracy), reaction speed (reaction). In addition to involving lecturers as research members, data collection was also carried out directly by the instructors who assisted in collecting the research data. The data on the results of this physical ability test include male athletes, as well as female athletes who took part in the selection, as well as second and third generation athletes. It should be noted that in the training program there are regulations that stipulate that if within a certain period of time, for example when athletes take part in try outs and try ins, both at regional, national and international levels, if they do not excel then these athletes will be degraded, or the age has exceeded the stipulations. determined by the Ministry of Youth and Sports in participating in the National Student Sports Week (POPNAS) these athletes will be replaced with those who meet the age and achievement requirements.